2014
DOI: 10.1063/1.4863742
|View full text |Cite
|
Sign up to set email alerts
|

Inverse magnetocaloric effect in Mn2NiGa and Mn1.75Ni1.25Ga magnetic shape memory alloys

Abstract: Inverse magnetocaloric effect is demonstrated in Mn2NiGa and Mn1.75Ni1.25Ga magnetic shape memory alloys. The entropy change at the martensite transition is larger in Mn1.75Ni1.25Ga, and it increases linearly with magnetic field in both the specimens. Existence of inverse magnetocaloric effect is consistent with the observation that magnetization in the martensite phase is smaller than the austenite phase. Although the Mn content is smaller in Mn1.75Ni1.25Ga, from neutron diffraction, we show that the origin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 35 publications
2
14
0
3
Order By: Relevance
“…The M(T ) plot in a low applied magnetic field of 50 Oe for annealed bulk samples shown in Fig. 5(a) reveals M s , M f , A s , and A f for Mn 1.75 Ni 1.25 Ga as 139, 134, 160, and 175 K, respectively, whereas the corresponding temperatures for Mn 1.9 Ni 1.1 Ga are 264, 160, 230, and 315 K. The drop at M s is related to the large magnetocrystalline anisotropy and lower magnetization of the martensite phase in these MSMAs [10,18,24]. A comparison of x-ray powder-diffraction profiles of the as-ground powder samples and the same powder after it was annealed at 773 K for 10 h (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The M(T ) plot in a low applied magnetic field of 50 Oe for annealed bulk samples shown in Fig. 5(a) reveals M s , M f , A s , and A f for Mn 1.75 Ni 1.25 Ga as 139, 134, 160, and 175 K, respectively, whereas the corresponding temperatures for Mn 1.9 Ni 1.1 Ga are 264, 160, 230, and 315 K. The drop at M s is related to the large magnetocrystalline anisotropy and lower magnetization of the martensite phase in these MSMAs [10,18,24]. A comparison of x-ray powder-diffraction profiles of the as-ground powder samples and the same powder after it was annealed at 773 K for 10 h (Fig.…”
mentioning
confidence: 99%
“…The austenite phase of Mn excess Ni-Mn-In alloys is known to be ferromagnetic whereas the martensite phase is generally believed to be nonmagnetic (either paramagnetic or antiferromagnetic) [6,8,11], whereas in the Mn excess Ni-Mn-Ga alloys, both the austenite and the martensite phases are reported to be ferrimagnetic [10,[16][17][18]. Using high-resolution synchrotron and laboratory x-ray powder-diffraction (XRD) data, it is shown that the martensite structure can be stabilized by residual stresses over a wide temperature range well above A f in both alloy systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These kinds of alloys not only have a very large magneticfieldinduced strain (MFIS) [3] [4]), but also possess other useful properties in regard to martensitic phase transformation, such as their very large magnetocaloric effect (MCE) and strong magnetoresistance (MR) [5][6][7][8][9][10][11][12][13][14][15]. This very large MFIS is due primarily to the rearrangement of martensitic variants, but it is  Corresponding author: Qingxue Huang Email address: qxhuang_pd@163.com obtained only in single crystals.…”
Section: Introductionmentioning
confidence: 98%
“…В последние годы сплавы Гейслера системы Mn 2 NiZ (Z = Ga, In, Sn, Sb) привлекли большой интерес исследователей, как ферромагнитные сплавы с эффектом памяти формы (ЭПФ) и полуметаллы (ферроили ферримагнетики), вследствие интересных физических свойств и потенциального применения для создания магнитных актюаторов и спинтронных устройств [1][2][3][4][5][6][7][8][9][10]. Исследования данных сплавов были простимулированы открытием магнитоиндуцируемых деформаций (4%) в монокристалле Mn 2 NiGa, обладающим термоупругим мартенситным фазовым переходом (ФП) вблизи комнатной температуры -270 K, и высокой температурой магнитного ФП -588 K [1].…”
Section: Introductionunclassified